Tax Literacy: Basic Tax Education for MSMEs in Cipayung District, East Jakarta - Darmastuti, Dewi; Wibawaningsih, Ekawati Jati; Surbakti, Lidya Primta (Universitas Kristen Cipta Wacana, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia often face tax compliance. This problem is also experienced by MSME actors in Cipayung District, East Jakarta. A challenge addressed through a Community Service initiative aimed at strengthening foundational tax literacy. The program sought to enhance participants’ understanding of tax regulations, improve documentation accuracy, mitigate penalty risks, and promote business resilience. Conducted by accounting faculty and graduate students from Universitas Pembangunan Nasional